An enhanced SOCP-based method for feeder load balancing using the multi-terminal soft open point in active distribution networks. (15th December 2017) - Ji, Haoran; Wang, Chengshan; Li, Peng; Zhao, Jinli; Song, Guanyu; Ding, Fei; Wu, Jianzhong
Highlights: A multi-terminal SOP-based honeycomb structure of network was presented for ADNs. An interval control-based strategy was proposed to mitigate the feeder load unbalance. An enhanced SOCP-based approach was developed with improved accuracy and efficiency. Abstract: The integration of distributed generators (DGs) exacerbates the feeder power flow fluctuation and load unbalanced condition in active distribution networks (ADNs). The unbalanced feeder load causes inefficient use of network assets and network congestion during system operation. The flexible interconnection based on the multi-terminal soft open point (SOP) significantly benefits the operation of ADNs. The multi-terminal SOP, which is a controllable power electronic device installed to replace the normally open point, provides accurate active and reactive power flow control to enable the flexible connection of feeders. An enhanced SOCP-based method for feeder load balancing using the multi-terminal SOP is proposed in this paper. By regulating the operation of the multi-terminal SOP, the proposed method can mitigate the unbalanced condition of feeder load and simultaneously reduce the power losses of ADNs. Then, the original non-convex model is converted into a second-order cone programming (SOCP) model using convex relaxation. To tighten the SOCP relaxation and improve the computation efficiency, an enhanced SOCP-based approach is developed to solve the proposed model. Finally, case studies are performed on the modified IEEE 33-node system to verify the effectiveness and efficiency of the proposed method.